Evaporation: Bio‐Inspired Evaporation Through Plasmonic Film of Nanoparticles at the Air–Water Interface (Small 16/2014). Issue 16 (August 2014) - Wang, Zhenhui; Liu, Yanming; Tao, Peng; Shen, Qingchen; Yi, Nan; Zhang, Fangyu; Liu, Quanlong; Song, Chengyi; Zhang, Di; Shang, Wen; Deng, Tao
<x xml:space="preserve">Abstract</x> A bioinspired surface evaporation approach with enhanced energy efficiency is demonstrated by W. Shang, T. Deng, and co‐workers on page 3234. Inspired by the biological evaporation processes, this approach uses the self‐assembled films of gold nanoparticles at the air‐water interface that confine the plasmonic thermal energy to achieve efficient evaporation. The free‐floating nature of the film also enables the tracking of the evaporative energy with the retreating interface, which maximizes both the energy usage and the materials usage for the evaporation process. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>